Peran Akuntabilitas dan Transparansi dalam Pengelolaan Anggaran di Sekretariat Daerah Kabuapten Sumedang - Juliyanti, Indri; Zakaria , Adam; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study ains to analyze the role of accountability and transparency in budget management at the Regional Secretariat of Sumedang Regency. A qualitative descriptive method was applied, with data collected through in-depth interviews and document analysis. NVivo 12 software was used to identify dominant themes and patterns in the data. Accountability is demonstrated through regular reporting—such as LKIP, LPPD, and LKPJ—and supervision by the Inspectorate and Regional House of Representatives (DPRD). Transparency is reflected in the open disclosure of budget information and the use of digital systems like SIPD. However, challenges remain, including limited human resources, delays in reporting, and underutilization of public information platforms. The study recommends strengthening information systems and enhancing personnel capacity.